Development of infinite qualitative model framework for consumer product aesthetic design - Ibrahim, Mohd Qadafie (2021)
Most engineering design processes today are more focused on functional aspects of product design and do not take aesthetic elements into account. Therefore, they are often difficult to use, unattractive, and/or do not solve the intended problems. As for the designers, they are not well-equipped to properly include aesthetic considerations during their design process, even though the advantages are widely acknowledged. This study proposes an Infinitive Qualitative Method (IQM) that effectively combines together theories from multiple disciplines such as social sciences, mechanical engineering design, industrial design and marketing management. The need for the new design framework is more pronounced for small manufacturing companies due to limited resources and also a lack of design skills among their small workforces. In fact, this research study is motivated by discussions and suggestions by the owners of two small companies producing consumer products within the local manufacturing industry in Malaysia. The IQM framework consists of two main components: product design and product development. The product design process includes an exploratory phase comprised of three stages: vision, ideation, and 3D conceptual. As for aesthetics, it is fully embedded within these stages by using established aesthetic design tools. Conversely, for the product development process, it explains the progress from multiple disciplines that have been adapted to ensure an efficient development process for the product. Ultimately, both of these components are interlinked with each other at a point in the framework where the product design component provides a theoretical design foundation for various stages of progress before engineering, manufacturing, and marketing teams take in-charge. The validation of the IQM design framework is achieved through triangulation analysis of results from a conducted survey, controlled experiment, and full-scale case study. IQM design framework adapts the best combination of design tools and methods with a novel approach that can potentially lead to a much better-quality product design. The study's significant finding is that this design method will provide a simple, easy, yet comprehensive way for design engineers to create well-designed products. IQM addresses the lack of proper aesthetic considerations in current product design methods.